New species of Graphocaecilius Enderlein (Psocodea: ‘Psocoptera’: Lachesillidae) from Colombia - Arango, Stephania Sandoval; Obando, Ranulfo González; Aldrete, Alfonso Neri García (Zootaxa, 2016)
Three new species of Graphocaecilius Enderlein are here described and illustrated; the species were found in the Colombian departments of Valle del Cauca and Risaralda, raising to five the number of species of this genus in Colombia, making it the most species rich country for Graphocaecilius in South America. A key to the species in the genus is included.